Pharmacological Doses of Daily Ascorbate Protect Tumors from Radiation Damage after a Single Dose of Radiation in an Intracranial Mouse Glioma Model - Grasso, Carole; Fabre, Marie-Sophie; Collis, Sarah V.; Castro, M. Leticia; Field, Cameron S.; Schleich, Nanette; McConnell, Melanie J.; Herst, Patries M. (Frontiers in Oncology, 2014)
Pharmacological ascorbate is currently used as an anti-cancer treatment, potentially in combination with radiation therapy, by integrative medicine practitioners. In the acidic, metal-rich tumour environment, ascorbate acts as a pro-oxidant, with a mode of action similar to that of ionising radiation; both treatments kill cells predominantly by free radical-mediated DNA damage. The brain tumour, glioblastoma multiforme (GBM), is very resistant to radiation; radiosensitising GBM cells will improve survival of GBM patients. Here we demonstrate that a single fraction (6 Gy) of radiation combined with a one hour exposure to ascorbate (5 mM) sensitised murine glioma GL261cells to radiation in survival and colony-forming assays in vitro. In addition, we report the effect of a single fraction (4.5 Gy) of whole brain radiation combined with daily intra-peritoneal injections of ascorbate (1 mg/kg) in an intra-cranial GL261 glioma mouse model. Tumour-bearing C57BL/6 mice were divided into four groups: one group received a single dose of 4.5 Gy to the brain eight days after tumour implantation, a second group received daily intra-peritoneal injections of ascorbate (day 8-45 after implantation), a third group received both treatments and a fourth control group received no treatment. While radiation delayed tumour progression, intra-peritoneal ascorbate alone had no effect on tumour progression. Tumour progression was faster in tumour-bearing mice treated with radiation and daily ascorbate than those treated with radiation alone. Histological analysis showed less necrosis in tumours treated with both radiation and ascorbate, consistent with a radio-protective effect of ascorbate in vivo. Discrepancies between our in vitro and in vivo results may be explained by differences in the tumour micro-environment which determines whether ascorbate remains outside the cell, acting as a pro-oxidant or whether it enters the cells and acts as an anti-oxidant.